2020
DOI: 10.1111/jbi.13937
|View full text |Cite
|
Sign up to set email alerts
|

Historical biogeography identifies a possible role of Miocene wetlands in the diversification of the Amazonian rocket frogs (Aromobatidae: Allobates)

Abstract: Aim: We investigate the spatiotemporal context of the diversification of Allobates, a widespread genus of Amazonian frogs with high species diversity particularly in western Amazonia. We tested if that diversity originated in situ or through repeated dispersals from other Amazonian areas and if this diversification took place during or after the Pebas system, a vast lacustrine system occupying most western Amazonia between 23 and 10 million years ago (Mya). Location: Amazonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 69 publications
6
65
0
Order By: Relevance
“…Relationships of SD with air temperature and precipitation in these regions (Figures 7A,B) are consistent with contributing roles of both contemporary ecological and historical (time-integrated) macroevolutionary effects driving down aquatic species diversity at higher elevations (e.g., Lujan et al, 2013;Hazzi et al, 2018). Similarly, the history of topographic growth, as opposed to present-day topographic or climatic conditions, is thought to be more important to the evolution and enrichment of many terrestrial (Castroviejo-Fisher et al, 2014;Antonelli et al, 2018a;Azevedo et al, 2020;Réjaud et al, 2020;Igea and Tanentzap, 2021) and aquatic (Smith et al, 2010;Badgley et al, 2017) vertebrate faunas.…”
Section: General Macroecological Expectationssupporting
confidence: 65%
“…Relationships of SD with air temperature and precipitation in these regions (Figures 7A,B) are consistent with contributing roles of both contemporary ecological and historical (time-integrated) macroevolutionary effects driving down aquatic species diversity at higher elevations (e.g., Lujan et al, 2013;Hazzi et al, 2018). Similarly, the history of topographic growth, as opposed to present-day topographic or climatic conditions, is thought to be more important to the evolution and enrichment of many terrestrial (Castroviejo-Fisher et al, 2014;Antonelli et al, 2018a;Azevedo et al, 2020;Réjaud et al, 2020;Igea and Tanentzap, 2021) and aquatic (Smith et al, 2010;Badgley et al, 2017) vertebrate faunas.…”
Section: General Macroecological Expectationssupporting
confidence: 65%
“…With almost the entire eastern and southern parts (25%) of its extent being already deforested for agriculture, an unknown proportion of endemic species, and thus of the testimony of Amazonian history, has already vanished (Lovejoy & Nobre, 2019). Anuran clades have repeatedly been documented to harbour many unnamed species in Amazonia (Vacher et al, 2020) and to display strikingly allopatric distribution patterns that could provide crucial insights into Amazonia's past (Fouquet, Cassini, Haddad, Pech, & Rodrigues, 2014;R ejaud et al, 2020). This is notably the case of the Boana albopunctata species group (Caminer & Ron, 2014;Funk et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Both contemporary and historical drivers play important roles in explaining current patterns of diversity in Amazon taxa (Albert et al, 2021;Azevedo et al, 2020;Crouch et al, 2019;Coronado et al, 2015;Réjaud et al, 2020). Here, using a large data set on freshwater fish distribution in the Amazon River basin (Jézéquel, Tedesco, Bigorne, et al, 2020) and a recent phylogenetic supertree (Rabosky et al, 2018), we found marked and contrasting phylogenetic signatures of fish assemblages across the 97 sub-drainages covering the entire system, whatever the phylogenetic metric analysed (i.e.…”
Section: Discussionmentioning
confidence: 60%